POLA PEMBENTUKAN KARAKTER RELIGIUS PADA ANAK DALAM PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR - Fefdianti, Defi (TA'LIM : Jurnal Studi Pendidikan Islam, 2025)
This study aims to determine the steps taken by Islamic Religious Education teachers at Alifya Elementary School, Bondowoso, in Tamansari Village, Bondowoso District, Bondowoso Regency, East Java Province. This study is a descriptive qualitative study. The subjects were Islamic Religious Education teachers at Alifya Elementary School, Bondowoso. The informants were third-grade students, one teacher at Alifya Elementary School, and the principal. The study concluded that the pattern of religious character formation by Islamic Religious Education teachers among students at Alifya Elementary School is quite good because discipline is very common within the school environment. The pattern established by Islamic Religious Education teachers in disciplinary interactions can be applied in direct education, for example through teaching and learning activities, role models, motivation, and supervision during worship, through the habit of congregational Dhuha and Dzuhur prayers, and also indirectly by providing discipline to students to prevent them from engaging in harmful behavior in the community.